Potensi Kuantitatif dan Kualitatif 10 Galur Unggul Baru Padi Jenis Pandan Wangi - Jaenudin Kartahadimaja; Eka Erlinda Syuriani; Marlinda Apriyani (Jurnal Penelitian Pertanian Terapan, 2016)
Rice is a staple food that is very dominant for Indonesia. Production of rice in 2014 asmany as 70,85 million tons of milled rice, 0,61% lower than production in 2013. Oneway to increase production is the use of high yielding varieties. Polinela have toassemble ten new rice lines Pandan wangi species which have superior appearance.The research goal is to test the potential yield and quality of rice ten new rice strains.The study was conducted in Polinela for 6 months. The study was conducted usingRandomized Completely Block Design ( RCBD ).The treatment consisted of ten strainsof rice, is repeated three times. The variables measured were (1) dry milled grainyield per hectare; (2) the levels of amylose and amylopectin. Qualitative variablesmeasured were the texture and the smell of ricewith organoleptic method. Quantitativedata were analyzed by analysis of variance, if there is a difference between thetreatment continued with Test Honestly Significant Difference (HSD) on the real levelof 0.05. Heritability of quantitative variables were observed calculated to estimatewhether the variable-variable controlled bygenetic factors or environment?The resultsshowed the new rice lines Polinela assemblies have a range of potential outcomes ofmilled rice ( GKG ) between 6.47 to 9.79 tonnes/ha,amylose content is low tomoderate, very fluffier texture until fluffier rice.Keywords: yield potential, new rice strains